Rand-Quiz: Web-Based Quiz System with OTP Using KJY Password Generator - Koh, Jia Yee; Mohamad, Kamaruddin Malik; Ramli, Sofia Najwa (Applied Information Technology And Computer Science, 2023)
One-Time Password (OTP) is a security mechanism used to authenticate users when login into web applications or other sensitive operations. It is a unique code that is generated for each use and are only valid for a single login attempt. However, the common 6-digit code OTP is weak and vulnerable to attack. The Quiz system also called as Rand-Quiz, is secured with a unique OTP by using KJY Password Generator. KJY Password Generator generates random values for OTP using combination of user ID, username, and user password. The Quiz system is featured with mail-based OTP, which will be sent to the user of the system for each time user login. This unique randomized mail-based OTP helps to improve security for the Rand-Quiz, web-based Quiz system.